PENERAPAN KESEPAKATAN KELAS DALAM PENCEGAHAN PRAKTIK BULYING di SDN 166 AMBAWA KABUPATEN LUWU TIMUR - Marta; Badruddin Kaddas; Maulidnawati Jumrah, Abrina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to describe the implementation of classroom agreements in preventing bullying at SDN 166 Ambawa, East Luwu Regency, and to identify the supporting and inhibiting factors affecting their implementation. This study employed a descriptive qualitative approach involving the principal, teachers, and students as research participants. Data were collected through observations, interviews, and documentation, and analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. Data validity was ensured through source triangulation, technique triangulation, and member checking. The findings reveal ed that classroom agreements were implemented through three stages: participatory formulation, consistent implementation, and regular evaluation. Their implementation reduced verbal and physical bullying, enhanced students' mutual respect, encouraged reporting of bullying incidents, and fostered a positive classroom culture. The implementation was supported by collaboration among the school, parents, teachers, and the principal, while geographical conditions, the use of local languages, and cultural diversity posed challenges. Therefore, classroom agreements can serve as an effective preventive strategy for creating a safe, inclusive, and bullying-free learning environment in elementary schools.